2020
DOI: 10.1021/acs.jproteome.0c00316
|View full text |Cite
|
Sign up to set email alerts
|

Repurpose Open Data to Discover Therapeutics for COVID-19 Using Deep Learning

Abstract: There have been more than 2.2 million confirmed cases and over 120 000 deaths from the human coronavirus disease 2019 (COVID-19) pandemic, caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2), in the United States alone. However, there is currently a lack of proven effective medications against COVID-19. Drug repurposing offers a promising route for the development of prevention and treatment strategies for COVID-19. This study reports an integrative, network-based deep-learning metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(172 citation statements)
references
References 55 publications
(135 reference statements)
0
172
0
Order By: Relevance
“…43 A further computational biophysics study 44 suggested that toremifene might block interaction between ACE2 and the spike protein of SARS-CoV-2 and might inhibit nonstructural protein 14 of SARS-CoV-2 (figure 1), mechanistically supporting the drug's antiviral activities. The mean plasma concentration of toremifene during administration of 60 mg per day was 0•88 mg/L (2•17 µM) in post-menopausal patients with breast cancer 40 and the peak plasma concentration (>10 µM) of toremifene (60 mg per day) was approximately three-times the antiviral effect on SARS-CoV-2 (half-maximal inhibitory 43 In summary, toremifene, identified by CoV-KGE 35 and network medi cine 16 approaches, offers a potential drug candidate to be tested in COVID-19 clinical trials.…”
Section: Antiviral Drugsmentioning
confidence: 90%
See 2 more Smart Citations
“…43 A further computational biophysics study 44 suggested that toremifene might block interaction between ACE2 and the spike protein of SARS-CoV-2 and might inhibit nonstructural protein 14 of SARS-CoV-2 (figure 1), mechanistically supporting the drug's antiviral activities. The mean plasma concentration of toremifene during administration of 60 mg per day was 0•88 mg/L (2•17 µM) in post-menopausal patients with breast cancer 40 and the peak plasma concentration (>10 µM) of toremifene (60 mg per day) was approximately three-times the antiviral effect on SARS-CoV-2 (half-maximal inhibitory 43 In summary, toremifene, identified by CoV-KGE 35 and network medi cine 16 approaches, offers a potential drug candidate to be tested in COVID-19 clinical trials.…”
Section: Antiviral Drugsmentioning
confidence: 90%
“…47 Dexamethasone was identified as a top repur posed drug candidate by CoV-KGE. 35 The ran domised trial 48…”
Section: Host-targeting Therapymentioning
confidence: 99%
See 1 more Smart Citation
“… 149 In addition, Zeng et al demonstrated that deep learning is a powerful methodology to prioritize existing drugs for further investigation. 150 Using a library of commercially available compounds, Elmezayen et al discovered several potential inhibitors against 3CLpro or TMPRSS2 with virtual screening and further evaluated their absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiles. 151 It can be expected that computer-screening of compounds and modeling will be increasingly used in the discovery of drugs for COVID-19 and other viral infections to expedite the drug development process and lower its cost.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Predicting potential links in heterogeneous biomedical networks (HBNs) can be beneficial to various significant biology and medicine problems, such as target identification, drug repositioning, and adverse drug reaction predictions. For example, network-based drug repositioning methods have already offered promising insights to boost the effective treatment of COVID-19 disease (Zeng et al 2020; Xiaoqi et al 2020), since it outbreak in December of 2019. Many network-based learning approaches have been developed to facilitate link prediction in HBNs.…”
Section: Introductionmentioning
confidence: 99%